Induced Local and Systemic Defense Responses in Tomato Underlying Interactions Between the Root-Knot Nematode Meloidogyne incognita and the Potato Aphid Macrosiphum euphorbiae - Mbaluto, Crispus M.; Ahmad, Esraa M.; Mädicke, Anne; Grosser, Katharina; van Dam, Nicole M.; Martínez-Medina, Ainhoa (Frontiers in Plant Science, 2021)
Plants mediate interactions between different herbivores that attack simultaneously or sequentially aboveground and belowground organs. The local and systemic activation of hormonal signaling pathways and the concomitant accumulation of defense metabolites underlie such aboveground-belowground interactions. The main plant-mediated mechanisms regulating these reciprocal interactions via local and systemic induced responses remain poorly understood. We investigated the impact of root infection by the root-knot nematode Meloidogyne incognita at different stages of its infection cycle, on tomato leaf defense responses triggered by the potato aphid Macrosiphum euphorbiae. In addition, we analyzed the reverse impact of aphid leaf feeding on the root responses triggered by the root-knot nematode. We focused specifically on the signaling pathways regulated by the phytohormones jasmonic acid (JA), salicylic acid (SA), abscisic acid (ABA), and indole-3-acetic acid (IAA) as well as steroidal glycoalkaloids as induced defense compounds. We found that aphid feeding did not induce aboveground hormonal signaling, but it repressed steroidal glycoalkaloids related responses in leaves, specifically when feeding on plants in the vegetative stage. Root infection by root-knot nematodes impeded the aphid-triggered repression of the steroidal glycoalkaloids related response aboveground. In roots, the root-knot nematode triggered the SA pathway during the entire infection cycle and the ABA pathway specifically during its reproduction stage. Root-knot nematode infection also elicited the steroidal glycoalkaloids related gene expression, specifically when it was in the galling stage. Aphid feeding did not systemically alter the root-knot nematode-induced defense responses in roots. Our results point to an asymmetrical interaction between M. incognita and Ma. euphorbiae when co-occurring in tomato plants. Moreover the root-knot nematode seems to determine the root defense response regardless of a later occurring attack by the potato aphid aboveground.